2006
DOI: 10.1085/jgp.200509389
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Populations of HCN Pacemaker Channels Produce Voltage-dependent and Voltage-independent Currents

Abstract: Hyperpolarization-activated HCN pacemaker channels are critical for the generation of spontaneous activity and the regulation of excitability in the heart and in many types of neurons. These channels produce both a voltage-dependent current (Ih) and a voltage-independent current (Iinst or VIC). In this study, we explored the molecular basis of the voltage-independent current. We found that for the spHCN isoform, VIC averaged ∼4% of the maximum HCN conductance that could be activated by hyperpolarization. Cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 43 publications
7
62
0
1
Order By: Relevance
“…I h itself is slow and would not be considered a candidate for the mechanosensory transduction channel on the basis of short response latencies of mechanosensory transduction in vertebrate hair cells (38), although activation of I h by stretch stimulus has recently been demonstrated, with stretch accelerating both activation and deactivation (39). I inst coded for by all of the HCN isoforms is both fast and voltage-independent and is blocked along with I h by ZD7288 (29,40). Another interesting aspect of the HCN instantaneous current is that it is enhanced by prior hyperpolarization pulses (27), with possible applicability to low frequency spontaneous oscillation of hair bundles associated with mechanosensory transduction (41).…”
Section: Discussionmentioning
confidence: 99%
“…I h itself is slow and would not be considered a candidate for the mechanosensory transduction channel on the basis of short response latencies of mechanosensory transduction in vertebrate hair cells (38), although activation of I h by stretch stimulus has recently been demonstrated, with stretch accelerating both activation and deactivation (39). I inst coded for by all of the HCN isoforms is both fast and voltage-independent and is blocked along with I h by ZD7288 (29,40). Another interesting aspect of the HCN instantaneous current is that it is enhanced by prior hyperpolarization pulses (27), with possible applicability to low frequency spontaneous oscillation of hair bundles associated with mechanosensory transduction (41).…”
Section: Discussionmentioning
confidence: 99%
“…9). This is not altogether surprising when one considers that HCN2 channels are partially open at this potential (Chen et al, 2001a) and may generate a voltage-independent current (Proenza et al, 2002;Macri and Accili, 2004;Proenza and Yellen, 2006). Another possible explanation for this effect is poor dendritic voltage control when recording from the soma, which could result from the nonisopotentiality of RTN neurons (Destexhe et al, 1996).…”
Section: Hcn2 Channels and Glur4-containing Ampa Receptors Are Presenmentioning
confidence: 99%
“…The two components of HCN-channel currents, the instantaneous current and the slowly developing component, are supposed to flow through two distinct channel populations (22). The instantaneous current is voltageindependent and accompanies expression of HCN2 and HCN1 channels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the voltage sensors and the gate molecularly failed to couple in instantaneous current-producing HCN channels (22). Figure 1C showed that in addition to the blockade of the voltage-dependent current, ZD7288 (one of the HCN-channel blockers) also blocked the inward instantaneous current at hyperpolarized potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation